Explaining, Interpreting, and Theorizing Religion and Myth : Contributions in Honor of Robert A. Segal - Roubekas, Nickolas P.,; Ryba, Thomas, (Supplements to Method & Theory in the Study of Religion ;, 2020)
In Explaining, Interpreting, and Theorizing Religion and Myth: Contributions in Honor of Robert A. Segal , nineteen renowned scholars offer a collection of essays addressing the persisting question of how to approach religion and myth as academic categories. Taking their cue from the work of Robert A. Segal, they discuss how to theorize about religion and myth from a variety of disciplinary perspectives. With cases from ancient Greece and Mesopotamia to East Asia and the modern world by and large, and engaging with diverse disciplines such as psychology, philosophy, anthropology, history, film, theology, and religious studies among others, the volume establishes a synthesis that demonstrates the pervasiveness as well as the pitfalls of the categories "religion" and "myth" in the world.